Book Review: Daschuk, J. (2013). Clearing the Plains: Disease, Politics of Starvation, and the Loss of Aboriginal Life - Boateng, Godfred O. (International Indigenous Policy Journal, 2016)
This article is a critical review of James Daschuk's book, Clearing the Plains: Disease, Politics, Starvation, and the Loss of Aboriginal Life.